Evaluasi Kapasitas Terminal Penumpang Bandar Udara Internasional Sultan Syarif Kasim II Kota Pekanbaru Provinsi Riau - Ella Silvana Chebelita; Zainuri; Rahmat, Hendri (JURNAL TEKNIK, 2024)
Sultan Syarif Kasim II International Airport located in Pekanbaru City with a terminal area of 28,600.48 m². in 2018 experienced overcapacity of 4,139,345 passengers where the terminal capacity only accommodates 3.5 million so that passenger forecasting is needed for the following year. Researchers aim to determine international and domestic passenger forecasting and analyze the level of service of check-in facilities, waiting rooms and baggage claim areas. Where using the trend moment method for forecasting the next 15 years, namely until 2038 using IATA standards. The results obtained from passenger forecasting are for the year 2038 international with a total of 885,081 passengers and domestic with a total of 2,418,834 passengers. Level of service analysis obtained in the existing conditions of the check-in facility with LOS A (excellent) and LOS C (good) values. For waiting room facilities with LOS A (excellet), LOS B (high) and LOS C (good). As for the baggage claim area facilities, the value of LOS A (excellent), LOS B (high) and LOS C (good). Researchers suggest conducting similar research with different methods throughout the airport facilities.